2021
DOI: 10.1038/s41550-021-01305-3
|View full text |Cite|
|
Sign up to set email alerts
|

A concordance scenario for the observed neutrino from a tidal disruption event

Abstract: During a tidal disruption event, a star is torn apart by the tidal forces of a supermassive black hole, with about 50% of the star's mass eventually accreted by the black hole. The resulting flare can, in extreme cases of super-Eddington mass accretion, result in a relativistic jet [1][2][3][4] . While tidal disruption events have been theoretically proposed as sources of high-energy cosmic rays 5,6 and neutrinos 7-14 , stacking searches indicate that their contribution to the diffuse extragalactic neutrino fl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
56
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(65 citation statements)
references
References 48 publications
(78 reference statements)
5
56
0
Order By: Relevance
“…These are checked to see whether they belong to populations that have been proposed as possible cosmic-ray and neutrino sources. Such populations include Gamma-Ray Bursts (GRBs) [32], supernovae with evidence of circumstellar medium interaction [33] or choked jets [34], Active Galactic Nuclei (AGN) [35] and in particular blazars [36], and TDEs [37][38][39][40][41][42][43][44][45][46][47]. Right: Properties of the neutrinos observed in that period, from [28].…”
Section: Pos(icrc2021)009mentioning
confidence: 99%
“…These are checked to see whether they belong to populations that have been proposed as possible cosmic-ray and neutrino sources. Such populations include Gamma-Ray Bursts (GRBs) [32], supernovae with evidence of circumstellar medium interaction [33] or choked jets [34], Active Galactic Nuclei (AGN) [35] and in particular blazars [36], and TDEs [37][38][39][40][41][42][43][44][45][46][47]. Right: Properties of the neutrinos observed in that period, from [28].…”
Section: Pos(icrc2021)009mentioning
confidence: 99%
“…See Ref. [1] for details of the model. This contains actually two factors: the fraction converted into non-thermal protons, and a spectral index-dependent bolometric correction because only a small fraction of particles will reach the highest energies.…”
Section: A Jetted Concordance Scenariomentioning
confidence: 99%
“…Our recent work, Ref. [1], gives an interpretation in terms of a relativistic jet, which could be be off-axis (see [5]); we refer to [6] for an overview of all models.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A TDE typically results from an orbiting star approaching its hosting supermassive black hole (SMBH) closely enough to be disrupted by the gravitational forces. Recently published studies (Stein et al 2021;Winter & Lunardini 2021) highlight the importance of these events for transient astronomy, through the very bright, long-lasting flares that extend over a broad wavelength spectrum. The possible association of neutrinos with TDEs (Stein et al 2021) triggered renewed interest in this research direction, to be confirmed by future observations.…”
Section: Tidal Disruption Events (Tdes)mentioning
confidence: 99%